Scleroderma Renal Crisis and Musculoskeletal Corticosteroid Injections - Muruganandam, Maheswari; Akpan, Eyerusalem B; McElwee, Matthew K; Emil, N Suzanne; Keller, Meredith C; Vangala, Adarsh S; Dihowm, Fatmah; Nunez, Sharon E; Gibb, James I; O'Sullivan, Frank X; Fields, Roderick A; Sibbitt, Jr, Wilmer L (Journal of clinical rheumatology, 2025)
Inflammatory arthritis frequently affects patients with systemic sclerosis (SSc) but musculoskeletal corticosteroid (MSKC) injections are often avoided due to concerns of scleroderma renal crisis (SRC). This study investigated the incidence of SRC following MSKC injections. In a 136-SSc cohort, 46 subjects underwent a total of 330 MSKC injections each receiving a significant dosage of triamcinolone acetonide (mean, 95.2 ± 44.2 mg per injection session). Data on blood pressure (BP), serum creatinine and glucose, urine protein, and complications were obtained before and after injection from the patients' medical records. MSKC and control subjects were similar in age (MSKC: 58.9 ± 12.1 vs. 55.5 ± 14.9 years), female (MSKC: 97.8% [45/46] vs. 89.9% [81/90]), antinuclear antibody (MSKC: 71.7% [33/46] vs. 81.1% [73/90]), anti-centromere antibody (MSKC: 47.8% [22/46] vs. 37.8% [34/90]), anti-topoisomerase antibody (MSKC: 26.1% [12/46] vs. 26.7% [24/90]), and anti-RNA polymerase III antibody (MSKC: 17.4.1% [8/46] vs. 24.4% [22/90]) (all p > 0.05). Pre- and post-MSKC demonstrated nonsignificant changes in systolic BP (pre: 127 ± 22 vs. post: 127 ± 21 mm Hg, p = 1.0), diastolic BP (pre: 71 ± 13 vs. post: 71 ± 11 mm Hg, p = 1.0), creatinine (pre: 0.78 ± 0.56 vs. post: 0.76 ± 0.20 mg/dL, p = 0.64), glucose (pre: 100 ± 21 vs. post: 99 ± 24 mg/dL, p = 0.67), and urine protein-creatinine ratio (pre: 0.14 ± 0.12 vs. post: 0.12 ± 0.11 mg/mg, p = 0.41). One case of SRC with mortality occurred in the controls and none in the MSKC group. No infections, hematologic abnormalities, or tendon rupture were noted. MSKC injections in established SSc are generally safe with low incidences of SRC and complications. However, it is still prudent to monitor high-risk individuals and recent-onset SSc post-MSKC injection.